From Aristotle’s Four Causes to Aquinas’ Ultimate Causes of Being: Modern Interpretations - Mitchell, Jason A. (Alpha Omega, 2014)
Summary: Over time, Aristotle’s theory of four causes lost some of their original flexibility as an instrument to be applied analogically in diverse sciences. Enrico Berti’s distinction between physical and metaphysical causality in Aristotle provides insight into overcoming this crystallization. More importantly, the novelty of Aquinas’ metaphysics of actus essendi calls for a revision of the four causes: first, actus essendi is presented as actuating act and the source of the finite being’s ordered operation; the substantial essence falls to potency and specifies the act of being; the efficient cause is the power of God insofar as he produces and moves the creature; divine exemplar causality is twofold (divine ideas as extrinsic measuring causes and divine nature as imitated); the final causality concerns both the order and the governance of the world. In this paper, then, I outline this analogical passage from Aristotle’s physical causality to Aquinas’ metaphysical causality in reference to their modern interpreters, like Enrico Berti and Jan A. Aertsen. Sommario: Col tempo, la teoria di Aristotele delle quattro cause ha perso un po’ della sua flessibilità originaria come uno strumento da essere applicato in modo analogico in diverse scienze. La distinzione fra una causalità física e una causalità metafísica in Aristotele fatta da Enrico Berti ci offre una via per superare questa cristalizzazione. Anzi, la novità della metafísica dell’Aquinate di actus essendi esige una rivisione delle quattro cause: in primo luogo, l’actus essendi si presenta come atto attuante e come la fonte dell’operazione ordinata dell’ente finito; l’essenza sostanziale cade a potenza e specifica l’atto di essere; la causa eficiente è la potenza divina in quanto produce e muove la creatura; la causalità divina esemplare è doppia (le idee di-vine come cause misuranti estrinseci e la natura divina come imitata); la causalità finale verte sull’ordine e sul governo del mondo. In questo articolo, quindi, presento una bozza di questo passaggio analogico dalla causalità fisica aristotélica e la causalità metafisica tomistia, facendo riferimento agli interpreti moderni, come Enrico Berti e Jan A. Aertsen.